Global health economics shaping health policy in low- and middle-income countries - Moreno-Serra, Rodrigo; Revill, Paul; Sculpher, Mark J.; Suhrcke, Marc (World Scientific series in global healthcare economics and public policy, 2019)
Provides up-to-date research on the theories and applications of health economics. Presents approaches to health economics developed at the University of York which are recognized for their high quality and distinction. Possesses practical tools and methods in dealing with health care challenges faced by LMIC countries"--